2017
DOI: 10.31018/jans.v9i1.1182
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, heritability and genetic advance for various quantitative and qualitative traits in Chilli (Capsicum annuum L.)

Abstract: Genetic variability, heritability and genetic advance for different quantitative and qualitative characters were studied in 64 genotypes of chilli. The study indicated the existence of considerable amount of genetic variability for all the traits under study. Analysis of variance revealed significant differences among genotypes for almost all the traits studied. The maximum range was recorded for fruit yield per plant (150-900 g) followed by vitamin-C content at red ripe stage (35.50 -207.17 mg/100g), vitamin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
3
2
0
3
Order By: Relevance
“…High heritability was observed for all the traits considered in the study Similar results on high heritability have also been reported in chilli by Chattopadhyay et al (2011) for days to 50 per cent flowering, green fruit length and girth, no of fruits per plant, green fruit yield per plant, dry fruit yield per plant, ascorbic acid content, oleoresin content and capsaicin content, Zehra et al (2017) for days to first green fruit harvest, days to first ripe fruit harvest, plant height, fruit length, fruit diameter, average fruit weight, number of fruits per plant and cap-saicin content.…”
Section: Heritability and Genetic Advancesupporting
confidence: 85%
See 1 more Smart Citation
“…High heritability was observed for all the traits considered in the study Similar results on high heritability have also been reported in chilli by Chattopadhyay et al (2011) for days to 50 per cent flowering, green fruit length and girth, no of fruits per plant, green fruit yield per plant, dry fruit yield per plant, ascorbic acid content, oleoresin content and capsaicin content, Zehra et al (2017) for days to first green fruit harvest, days to first ripe fruit harvest, plant height, fruit length, fruit diameter, average fruit weight, number of fruits per plant and cap-saicin content.…”
Section: Heritability and Genetic Advancesupporting
confidence: 85%
“…Analysis of variance for different traits in chilliChattopadhyay et al (2011) for oleoresin content,Zehra et al (2017) for dry yield as percentage of fresh ripe andAmit et al (2014) for average fruit weight.…”
mentioning
confidence: 99%
“…Nilai koefisien keragaman genotipe dapat memberi informasi mengenai keragaman genotipe dari suatu tanaman sehingga dapat diketahui tingkat keluasan dalam pemilihan genotipe. Melalui informasi heritabilitas, pemulia dapat menentukan sejauh mana intensitas seleksi yang dilakukan untuk memisahkan pengaruh lingkungan terhadap fenotipe suatu tanaman (Zehra et al, 2017).…”
Section: Pendahuluanunclassified
“…Heritabilitas juga digunakan untuk menentukan sejauh mana suatu karakter dapat diwariskan dari tetua kepada turunannya. Melalui informasi heritabilitas, memungkinkan pemulia dalam menentukan sejauh mana intensitas seleksi yang dilakukan untuk memisahkan pengaruh lingkungan terhadap fenotipe suatu tanaman (Zehra et al, 2017). Yunandra et al (2017) melaporkan bahwa karakter bobot buah per tanaman pada cabai memiliki heritabilitas arti sempit sedang, sedangkan karakter jumlah buah per tanaman memiliki heritabilitas arti sempit rendah.…”
Section: Pendahuluanunclassified
“…Hal ini mengindikasikan peranan faktor genetik lebih besar dibandingkan faktor lingkungan dalam mempengaruhi penampilan suatu tanaman dan sifat-sifat tersebut dapat terwariskan pula pada generasi selanjutnya. Beberapa penelitian juga menunjukkan karakter hasil dan komponen hasil memiliki nilai heritabilitas arti luas tinggi, yaitu karakter bobot buah per tanaman (Adday, 2016), jumlah buah per tanaman (Hastuti et al, 2016), bobot per buah (Singh et al, 2017), umur panen, dan panjang buah (Zehra et al, 2017).…”
Section: Heritabilitas Pada Karakter Dan Komponen Hasilunclassified